Gabungan Kelompok Tani (GAPOKTAN) Memiliki Peran Dalam Memajukan Ekonomi Masyarakat - Rosidin, Masrul; Sumpena, Deden; Aliyudin, Aliyudin (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2023)
The Association of Farmers Groups (Gapoktan) is an organization consisting of farmer groups that have the same goal. The purpose of this research is to know the Gapoktan program in advancing the community’s economy, to find out the Gapoktan steps in advancing the community’s economy, to find out the results of Gapoktan activities in advancing the community’s economy. This study uses qualitative methods and descriptive. There are five research results from the programs implemented by Gapoktan Anugerah in advancing the community’s economy, namely socialization and delivery of agricultural information, holding partnership programs, providing agricultural needs, collective marketing of products, and conducting training programs. There are three steps taken by Anugerah Gapoktan, namely awareness, development and empowerment. The results obtained from these activities, Gapoktan Anugerah aims to achieve changes for the better for farmers around Pangalengan both for members and the surrounding community.